2018
DOI: 10.3233/cbm-181287
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of TNM staging and lymph node metastasis of gastric cancer with MRI features and VEGF expression

Abstract: The VEGF protein expression in gastric cancer tissues is positively correlated with TNM staging and lymph node metastasis in patients. The preoperative prediction results of MRI are well consistent with postoperative pathological results, and MRI features are correlated with lymph node metastasis in patients, which has an important guiding significance for the diagnosis and treatment of gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 17 publications
1
25
0
1
Order By: Relevance
“…In this study, ETAR overexpression was also associated with reduced survival time as determined by univariate and multivariate analyses. Similarly, and consistent with previous studies, age, tumor size, depth of invasion, lymph node and distant metastasis, and VEGF expression were all significantly associated with poor prognosis of gastric cancer patients . Our findings are also in agreement with earlier reports that correlated elevated expression of ETAR with the progression and poor prognosis in many tumors .…”
Section: Discussionsupporting
confidence: 93%
“…In this study, ETAR overexpression was also associated with reduced survival time as determined by univariate and multivariate analyses. Similarly, and consistent with previous studies, age, tumor size, depth of invasion, lymph node and distant metastasis, and VEGF expression were all significantly associated with poor prognosis of gastric cancer patients . Our findings are also in agreement with earlier reports that correlated elevated expression of ETAR with the progression and poor prognosis in many tumors .…”
Section: Discussionsupporting
confidence: 93%
“…a-c qRT-PCR and western blotting analysis results showed that MCU expression was silenced by two MCU-siRNAs in HCT-116 and SW-480 cells. d Representative immunofluorescence images showing HIF-1α expression in HCTmetastasis, and clinical pathological prognosis (Pang et al 2018). Previous research found that knockdown of Piezo1 attenuated migration of human umbilical vein endothelial cells towards VEGF (Li et al 2014).…”
Section: Discussionmentioning
confidence: 97%
“…Li et al 37 reported that VEGF expression led to colon cancer metastasis. In addition, in gastric cancer, VEGF expression is also correlated with TNM staging and lymph node metastasis 38 . Moreover, distant metastasis and poor prognosis are related to VEGF in osteosarcoma, ovarian cancer and breast cancer 39 - 41 .…”
Section: Discussionmentioning
confidence: 99%